Penentuan Strategi Bersaing UKM Mitra Usaha Bakso Menggunakan Analisis SWOT - Ria Rizki Rahmawati; Mohammad Satori; Puti Renosori (UNISBA Press, 2024)
Abstract. UKM (Usaha Kecil Menengah) is a term commonly used to refer to small and medium-sized businesses. UKM s generally operate on a smaller scale compared to large corporations and play a crucial role in the economy. However, UKM MUB is currently facing challenges, as its income has decreased in the last 6 months. According to the owner of UKM MUB, the decline in income is attributed to the high number of competitors producing similar products and the suboptimal promotion conducted by the company. Therefore, there is a need for a competitive strategy using the External Factor Evaluation (EFE) with a matrix of external strategic factors using the SWOT method. The analysis results indicate that the highest weight is for the strength factor of the distinctive taste of the offered product = 0.11, while the lowest is for the good relationship between consumers and producers = 0.06. The highest weight for weakness factors is the limitation of capital = 0.1, and the lowest is for frequently faulty machines, lack of innovation in product variation, and difficulty in obtaining some raw materials = 0.05. The highest weight for opportunity factors is the high demand at certain times = 0.25, and the lowest is the kredit usaha rakyat program assisting in developing UKMs = 0.15. The highest weight for threat factors is the innovation and diversity of competitors' products = 0.2, and the lowest is the presence of many competitors in the same field = 0.09. Based on the Cartesian diagram's subtotal score difference between strength and weakness factors and opportunity and threat factors being positive (+), the suitable competitive strategy for the company is growth (strength opportunity). This involves developing products by adding variations and conducting promotions using advertising techniques to increase daily demand. Abstrak. UKM (Usaha Kecil Menengah) merupakan sebuah istilah yang sering digunakan untuk merujuk pada bisnis kecil dan menengah. UKM umumnya memiliki skala yang lebih kecil dibandingkan dengan perusahaan besar dan memainkan peran penting dalam ekonomi. Namun, UKM MUB memiliki permasalahan yang harus dihadapi dimana pendapatan selama 6 bulan terakhir mengalami penurunan. Dari hasil wawancara dengan pemilik UKM MUB menurunnya pendapatan disebabkan banyaknya pesaing yang memproduksi produk yang sama dan promosi yang dilakukan oleh perusahaan belum optimal. Maka, diperlukannya strategi bersaing dengan nilai EFE (External Factor Evaluation) yang dibutuhkan matriks faktor strategi eksternal dengan metode SWOT. Dari hasil analisis, bahwa bobot tertinggi faktor kekuatan produk yang ditawarkan memiliki ciri khas dari segi rasa = 0,11 dan terendah hubungan baik yang terjalin antara konsumen dan produsen = 0,06. Bobot tertinggi faktor kelemahan keterbatasan modal = 0,1 dan terendah mesin yang kerap kali rusak, kurang berinovasi dalam membuat variasi produk, beberapa bahan baku sulit didapatkan = 0,05. Bobot tertinggi faktor peluang jumlah permintaan tinggi pada waktu tertentu = 0,25 dan terendah program kredit usaha rakyat membantu mengembangkan UKM = 0,15. Bobot tertinggi faktor ancaman produk pesaing lebih inovatif dan beragam = 0,2 dan terendah banyak pesaing di bidang yang sama = 0,09. Pada skor bobot penentuan strategi bersaing yang cocok untuk perusahaan berdasarkan digram kartesius adalah growth (strenght opportunity), karena selisih antara sub total dari skor bobot faktor kekuatan dengan kelemahan dan faktor peluang dengan ancaman bernilai positif (+) dengan jenis strategi mengembangkan produk dengan menambahkan variasi dan melakukan promosi menggunakan teknik periklanan untuk meningkatkan permintaan setiap harinya.